Recurrent Hypokalemia and Adrenal Steroids in Patients With APECED - Borchers, Joonatan; Mäkitie, Outi; Jääskeläinen, Jarmo; Laakso, Saila (Frontiers in Endocrinology, 2022)
Context: Hypokalemia is a common finding in patients with autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) but its exact cause often remains unknown. Objective: To explore the prevalence and etiology of hypokalemia and the role of adrenal steroids therein in a cohort of patients with APECED. Methods: We performed a cross-sectional assessment and retrospective data collection of 44 Finnish patients with APECED to identify subjects with episodes of hypokalemia. Also 68 healthy matched controls attended the cross-sectional evaluation. Factors associating with a tendency for hypokalemia were analyzed by reviewing medical records during 1960-2021 and performing a cross-sectional analysis of serum adrenal steroids. Results: In total 14 of the 44 APECED patients (32%) had episodes of hypokalemia; 2 presented with hypokalemia at cross-sectional evaluation and 12 had a history of hypokalemia before the cross-sectional evaluation. Hypokalemic episodes started at the median age of 14.1 years; 12/14 (86%) had primary adrenal insufficiency (PAI). The median number of hypokalemic periods per year was 0.3 (range 0.04-2.2); the frequency correlated positively with the number of clinical APECED manifestations at the time of cross-sectional evaluation (r=0.811, P<0.001). Etiologies of hypokalemia varied but episodes often occurred when new clinical manifestations developed and during hospitalizations. Three patients had kidney defects, also associated with electrolyte imbalances. Severity of hypokalemia varied (range 2.2-3.2 mmol/L), but no severe complications were observed. At cross-sectional evaluation, patients with PAI (30/44) had significantly lower median plasma potassium and higher sodium concentration than controls, suggesting that fludrocortisone treatment contributed to hypokalemia. Detailed analysis of adrenal steroids provided no conclusive differences between patients with and without episodes of hypokalemia. Conclusions: In APECED, hypokalemia is common and varies in terms of frequency, etiology, and severity. PAI and kidney disease predispose to hypokalemia. In addition, hypokalemic periods seem to be more common in patients with more severe phenotype of APECED.